FEASIBILITY STUDY ON CONDUCTING A MEDICAL CAMP IN WASHIM DISTRICT, MAHARASHTRA - Dr.K.Rao Prashanth Jyoty; Ms.K. Prathyusha Rao; Ms.Sharmila; Ms.Subitsha (International Conference on Multidisciplinary Research Perspective, 2025)
HHealthcare access in rural India remains limited due to poor infrastructure, lack of medical records, and weak sanitation facilities. This study examines the feasibility of conducting a medical camp in Washim District, Maharashtra. The objectives are to evaluate the sanitation practices of the community, analyse prevailing health conditions, and propose the creation of a robust digital and physical medical record system for every individual in the district. The study adopts a mixed-methods approach including surveys, interviews, observational analysis, and secondary data review. Findings indicate high prevalence of water-borne diseases, malnutrition, and inadequate sanitation facilities. Establishing medical camps, supported by a centralized health record system, can significantly improve preventive and curative healthcare delivery in Washim.